2004
DOI: 10.1158/0008-5472.can-03-4038
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Microenvironment Interactions

Abstract: These transfection experiments also indicated that manipulating the levels of the FX enzyme affected global cellular fucosylation and altered the interaction of colorectal cancer cells with some extracellular matrix components such as fibronectin. We also found that highly metastatic colorectal cancer variants express higher levels of FX and of sialyl Lewis-a than low metastatic variants originating in the same tumors. These results lead us to hypothesize that the FX enzyme controls the capacity of colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Each glass slide was treated with a fibronectin solution of 20μg/ml [56]. 270.000 HUVEC cells were suspended in 2 ml of EMB medium (Lonza), plated on each well and left o/n at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Each glass slide was treated with a fibronectin solution of 20μg/ml [56]. 270.000 HUVEC cells were suspended in 2 ml of EMB medium (Lonza), plated on each well and left o/n at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Most of our understanding of intracellular signaling has been gained in the analysis of transiently activated pathways as normally observed Also tumors do not function as isolated entities but have multiple signaling exchanges with the tumor environment. The interaction of cancer cells with other cells and/or components like the extracellular matrix of the microenvironment contribute to the survival and proliferation of tumor cells [55,56]. Therefore, pharmacological disruption of these interactions also represents a novel and increasingly important avenue for treatment of cancer and in particular of metastatic spread.…”
Section: Inhibition Of Intracellular Signaling For Therapeutic Purposmentioning
confidence: 99%
“…In contrast, our own group [6] and other authors [7] demonstrated specific tumor cell adhesion in the microcirculation of the liver and lung [8,9]. Furthermore, injected human colon cancer cells showed an organ specific pattern of cell adhesion in rats, mimicking the clinical picture of metastatic colon cancer [10].…”
Section: Introductionmentioning
confidence: 95%
“…Obviously, malignant cells originating from a variety of tissues differ with regard to available adhesion molecules for cell - cell or cell - ECM interactions. For example, E-Selectin mediated adhesion to endothelial cells has been established for inflammatory leucocytes as well as several human cancer cells [7-9]…”
Section: Introductionmentioning
confidence: 99%